1961
DOI: 10.1515/mamm.1961.25.4.528
|View full text |Cite
|
Sign up to set email alerts
|

Foramen Ovale and Ductus Arteriosus Botalli in Aquatic Mammals

Abstract: ment.retardée pâr râpport aux animaux terrestres. ces faits rotrt en rapport avec la t-ension en oxygène-du sâng.-L,élévation de celle_ci ap"ès ia orir.ao"e entraine I'occlusion du canal ; une ãéficience en oxygèn" "ri àî "ã"^i"J"" "ap^_ ble de ìtouvrir à nouveau. L'auteur examine la bio"rogie a", ",,i-u"" marins en fonction de ces diverses données et compare notamrnent les cétacés et re Phoque veau-marin aux a-utres pinnipèdes, dont res ¡"""", ,r"-p¿rr¿t""nt dans I'eau qu'âgés de 3-4 semaines au moins et parf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…vitulina pups enter the water almost immediately after birth to avoid predation (Lyderson et al, 2002;Burns, 2009), diving to a mean depth of 2.1 m (Greaves et al, 2005). Similar findings of prolonged patency compared to terrestrial animals have been briefly reported in cetaceans (Slipjer, 1961). Slipjer's necropsy findings demonstrated that anatomic d.a.…”
Section: Discussionmentioning
confidence: 73%
“…vitulina pups enter the water almost immediately after birth to avoid predation (Lyderson et al, 2002;Burns, 2009), diving to a mean depth of 2.1 m (Greaves et al, 2005). Similar findings of prolonged patency compared to terrestrial animals have been briefly reported in cetaceans (Slipjer, 1961). Slipjer's necropsy findings demonstrated that anatomic d.a.…”
Section: Discussionmentioning
confidence: 73%
“…The pulmonary veins in the roof of the left atrium also seem to be arranged in a way that facilitates the flattening of the tissue fold over the foramen. Despite this, however, there are reports of studies in the common seal (Phoca vitulina) which indicate that the foramen ovale of about 75 % of suckling pups may be open during the first 2-3 months of neonatal life (Rapp, 1837;Slijper, 1936Slijper, , 1961Van Nie and van der Kamp 1988). Why this should be is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Accounts of the anatomy of the ducti venosus and arteriosus of the seal have been given earlier (Owen, 1831 ;Hepburn 1909;Haig 1914;Slijper, 1936Slijper, , 1961. However, although the gross structure of the foramen ovale of a number of domestic and other terrestrial mammals has been commented upon (Mosca 1914;Amoroso et al 1942;Franklin et al 1942;Macdonald 1988;Macdonald et al 1988), there are very few descriptions of this structure in aquatic mammals (Slijper 1961). There are brief reports relating to the foramen ovale of pinnipeds in the early literature, indicating that it had been given some attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few cases of heart disease reported in cetaceans include infections (Guzmán-Verri et al 2012), parasites (Jardine & Dubey 2002), and malformations (Slijper 1961, Gray & Conklin 1974, Neurohr 1982, Troncone & Zizzo 1994, Powell et al 2009). Bossart et al (2007) reported cases of myocardial degeneration and moderate myocarditis in stranded sperm whales (Kogia spp.…”
Section: Introductionmentioning
confidence: 99%